2014
DOI: 10.1002/jmv.23910
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a change in the epidemiology of hepatitis B virus infection after nearly two decades of universal hepatitis B vaccination in South Africa

Abstract: The hepatitis B vaccine has been part of the South African Expanded Program on Immunization since April 1995 but its long-term impact remains unknown. This study tested 1,206 sera collected from patients aged 1-25 years from various health facilities across the country for HBV serological markers and HBV DNA. Based on the year the vaccine was introduced, samples were stratified by age into pre- and post-vaccine introduction populations, which were then compared for evidence of immunity and chronic carriage usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…Only one mother in that cohort was HBeAg positive [32]. Another cross-sectional study from South Africa comparing pre-and post-vaccination cohorts over an almost 20 year period showed a decrease in HBsAg prevalence from 4.2% to 1.4% [33].…”
Section: Discussionmentioning
confidence: 93%
“…Only one mother in that cohort was HBeAg positive [32]. Another cross-sectional study from South Africa comparing pre-and post-vaccination cohorts over an almost 20 year period showed a decrease in HBsAg prevalence from 4.2% to 1.4% [33].…”
Section: Discussionmentioning
confidence: 93%
“…From a previous health facility-based hepatitis B serosurvey [2], 201 serum samples which tested positive for serological makers of exposure to HBV; HBsAg and/or antibody to HBV core antigen (anti-HBc), were identified out of a total sample size of 1206. These serologically exposed samples were the focus of this study.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies have reported a decline in the prevalence of chronic HBV infection since the vaccine’s introduction [2,35,36]. What threatens the benefits of vaccination is the emergence of HBV S gene variants due to immune selection pressure from the HBV vaccine [50].…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, emerging data have outlined the beneficial impact of universal HBV vaccination. In South Africa, where HBV vaccination was introduced in 1995, immunity to HBV among subjects aged 1-25 years increased from 13 to 57 % in the post-vaccine era, resulting in a steady decline in HBsAg carriage from 4.2 to 1.4 % [55].…”
Section: Africamentioning
confidence: 99%